Working together as equals: collegiality expectations of academics at a public university in Malaysia - Zulkifly, Nurul Afiqah; Ismail, Ismi Arif; Asimiran, Soaib; Alias, Siti Noormi; Ismail, Maimunah (Routledge, 2021)
Universities in most countries have become more managerial as a consequence of a deliberated concept of collegiality. As one of the most vital assets of the institution, academics play an important role in developing and nurturing collegiality within faculties. This qualitative study explores collegiality expectations of 12 full-time academics. Insights obtained from the academics were analyzed using collegiality framework consisting of behavioral, cultural and structural collegiality. The participants highlighted many dimensions of collegiality categorized under several themes, namely social engagement, sense of collectivism, degree of autonomy, and authority. The findings of this study indicated that academics fundamentally expected to be treated as equals among their fraternities.